Supporting material for "Ambivalence, Avoidance and Appeal: Alliterative Aspects of Anglo Anthroponyms" - Bush, S (University of Oxford, 2020)
In England and Wales, birth, marriage and death (BMD) registration began in July 1837. BMD records were obtained from the ‘UK local BMD’ project (http://www.ukbmd.org.uk/local), a volunteer-led effort to transcribe the local indices of the UK BMD registers for digital preservation. Birth records spanning the complete years 1838-2014 were downloaded in September 2016 from the ‘UK local BMD’ as part of a previous study describing the application of network methods to onomastic data (Bush, et al. 2018; https://www.ncbi.nlm.nih.gov/pubmed/30379928). These records were then updated in January 2018 for a study describing the re-use of birth records in response to child bereavement (Bush, 2019; https://www.tandfonline.com/doi/abs/10.1080/00277738.2018.1536186). Employing the data used for the latter, 23,468,892 birth records were parsed to generate this dataset, which explores trends in alliterative naming within England and Wales. The dataset approximates 130,000 to 230,000 records per year from 1838-1950, 25,000 to 100,000 records per year from 1951-2000, and 5000 to 15,000 records per year from 2001 to 2014. This supplementary archive represents tables and figures drawn from analysis of this dataset. These are provided in support of the paper “Ambivalence, avoidance, and appeal: alliterative aspects of Anglo anthroponyms.” The website hosting the original UK local BMD data, www.ukbmd.org.uk, is operated by Weston Technologies Ltd (Crewe, Cheshire, UK), this company being the owner or license-holder of the intellectual property constituting the birth records. This data was used for the aforementioned studies pursuant to section 29A of the UK Copyright, Designs and Patents Act 1988, where a copyright exception permits copies to be made of lawfully accessible material in order to conduct text and data mining for non-commercial research. This archive contains no copies of any of the original birth records and nor does it present data in a form by which they may be reconstructed. In several countries, one of the most pronounced trends in contemporary baby naming is to choose a comparatively uncommon name. Nevertheless, although a well-documented phenomenon, studies of uncommon name use are often limited to forenames. This study analyses approximately 22 million full names from England and 1 million from Wales, given between 1838 and 2014. It addresses the hypothesis that, consistent with the contemporary desire to choose an uncommon name, alliterative names – uncommon by definition – would become increasingly popular. More broadly, this study charts the long-term trends in alliterative naming over time, which in both England and Wales is consistent with a random expectation for much of the 19th century but declines significantly throughout the 20th century to its lowest use in the 1970s. This trend reverses towards the end of the 20th century, with alliterative naming becoming more common in contemporary records. These three aspects of alliterative name use are thematically referred to as ‘ambivalence’, ‘avoidance’ and ‘appeal’, and may reflect changing attitudes towards alliterative naming. The relatively renewed appeal of alliterative names towards the end of the 20th century complements previous research on the preponderance of uncommon names and the contemporary ‘need for uniqueness’ in naming.